2014
DOI: 10.26687/archnet-ijar.v8i3.374
|View full text |Cite
|
Sign up to set email alerts
|

Observing Privacy, Modesty and Hospitality in the Home Domain: Three Case Studies of Muslim Homes in Brisbane, Australia

Abstract: A home embodies a sensorial space that is layered with personal memories and traces of history. The success of a home in providing a strong sense of place depends on various factors such as geographical location, climatic conditions, and occupants’ world-views and perceptions. This paper explores Muslims’ perceptions of privacy, modesty and hospitality within their homes through their lived experiences. This case study focuses on three Muslim families living in Australian designed homes within the same suburb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…In combination, these three principles form the primary considerations of those who seek to create a traditional Muslim home (Othman et al, 2014). However, the migration of Muslims across the globe also exposes them to the cultures and traditions of their host countries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In combination, these three principles form the primary considerations of those who seek to create a traditional Muslim home (Othman et al, 2014). However, the migration of Muslims across the globe also exposes them to the cultures and traditions of their host countries.…”
Section: Introductionmentioning
confidence: 98%
“…The design of traditional Muslim homes is subject to guidelines from principles outlined in Islamic Sharia Law, which are derived from the Quran (revelations of Allah to Prophet Muhammad) as well as hadiths and sunnahs (utterances and actions of Prophet Muhammad). Following three main principles have emerged from these guidelines (Othman et al, 2014;Omer, 2010;Mortada, 2011): a) privacy, a safe and private place for personal and family's sanctuary; b) modesty, a home with spaces for religious rituals and activities, further defined by humility in design through economical and sustainable designs, and; c) hospitality, a dwelling with opportunities to extend hospitality to neighbours and enhance relationships with the society.…”
Section: Introductionmentioning
confidence: 99%
“…Nia et al (2014) study how the vernacular roofs in Kashan, Iran have responded to people's behaviours by improving physical and mental health and offering spiritual and a spectrum of intangible benefits. Othman et al (2014) examine how the design of Muslim homes in Brisbane, Australia could achieve optimal privacy and extend hospitality to guests inside and outside their homes simultaneously.…”
Section: Archnet-ijar In 2014mentioning
confidence: 99%
“…The spatial organisation of the interior spaces at the houses in Amman had been affected by various cultural aspects such as religion, tribe traditions, and gender. Islam involves certain religious beliefs that are applied directly to the design of houses in Amman; these beliefs are derived from the Quran (the Muslims Holy book) and Hadith (the record of the words and actions of Prophet Muhammad) (Othman et al, 2014;Mortada, 2011;Campo, 1991). The images of houses expressed in the Quran and Hadith have shaped Muslim ideas about life and faith (Campo, 1991).…”
mentioning
confidence: 99%
“…In Islam, privacy requirements are usually met through precise design by separating the private life from the public relationships (Memarian and Toghr, 2011). Othman et al (2014) and Mortada (2011) suggested that privacy in traditional Muslim's houses comprises four layers: Privacy between neighbours, privacy between males and females, privacy between family members inside a house, and Individual privacy (Figure 1). Terms like privacy should be anchored with cultural sitting when discussing issues such as gender, space, and cultural dynamics.…”
mentioning
confidence: 99%